Withania somnifera modulates cancer cachexia associated inflammatory cytokines and cell death in leukaemic THP-1 cells and peripheral blood mononuclear cells (PBMC's) - Dhaneshree Bestinee Naidoo; Anil Amichund Chuturgoon; Alisa Phulukdaree; Kanive Parashiva Guruprasad; Kapaettu Satyamoorthy; Vikash Sewram (BMC, 2018)
Abstract Background Cancer and inflammation are associated with cachexia. Withania somnifera (W. somnifera) possesses antioxidant and anti-inflammatory potential. We investigated the potential of an aqueous extract of the root of W. somnifera (WRE) to modulate cytokines, antioxidants and apoptosis in leukaemic THP-1 cells and peripheral blood mononuclear cells (PBMC's). Methods Cytotoxcity of WRE was determined at 24 and 72 h (h). Oxidant scavenging activity of WRE was evaluated (2, 2-diphenyl-1 picrylhydrazyl assay). Glutathione (GSH) levels, caspase (− 8, − 9, − 3/7) activities and adenosine triphosphate (ATP) levels (Luminometry) were thereafter assayed. Tumour necrosis factor-α (TNF-α), interleukin (IL)-6, IL-1β and IL-10 levels were also assessed using enzyme-linked immunosorbant assay. Results At 24 h, WRE (0.2-0.4 mg/ml) decreased PBMC viability between 20 and 25%, whereas it increased THP-1 viability between 15 and 23% (p < 0.001). At 72 h, WRE increased PBMC viability by 27-39% (0.05, 0.4 mg/ml WRE) whereas decreased THP-1 viability between 9 and 16% (0.05-0.4 mg/ml WRE) (p < 0.001). Oxidant scavenging activity was increased by WRE (0.05-0.4 mg/ml, p < 0.0001). PBMC TNF-α and IL-10 levels were decreased by 0.2-0.4 mg/ml WRE, whereas IL-1β levels were increased by 0.05-0.4 mg/ml WRE (p < 0.0001). In THP-1 cells, WRE (0.05-0.4 mg/ml) decreased TNF-α, IL-1β and IL-6 levels (p < 0.0001). At 24 h, GSH levels were decreased in PBMC's, whilst increased in THP-1 cells by 0.2-0.4 mg/ml WRE (p < 0.0001). At 72 h, WRE (0.1-0.4 mg/ml) decreased GSH levels in both cell lines (p < 0.0001). At 24 h, WRE (0.2-0.4 mg/ml) increased PBMC caspase (-8, -3/7) activities whereas WRE (0.05, 0.1, 0.4 mg/ml) increased THP-1 caspase (-9, -3/7) activities (p < 0.0001). At 72 h, PBMC caspase (-8, -9, -3/7) activities were increased at 0.05-0.1 mg/ml WRE (p < 0.0001). In THP-1 cells, caspase (-8, -9, -3/7) activities and ATP levels were increased by 0.1-0.2 mg/ml WRE, whereas decreased by 0.05 and 0.4 mg/ml WRE (72 h, p < 0.0001). Conclusion In PBMC's and THP-1 cells, WRE proved to effectively modulate antioxidant activity, inflammatory cytokines and cell death. In THP-1 cells, WRE decreased pro-inflammatory cytokine levels, which may alleviate cancer cachexia and excessive leukaemic cell growth.